Place-Based Education in Geoscience: Theory, Research, Practice, and Assessment. Issue 4 (1st November 2017) - Semken, Steven; Ward, Emily Geraghty; Moosavi, Sadredin; Chinn, Pauline W. U.
ABSTRACT: Place-based education (PBE) is a situated, context-rich, transdisciplinary teaching and learning modality distinguished by its unequivocal relationship to place, which is any locality that people have imbued with meanings and personal attachments through actual or vicarious experiences. As an observational and historical science, geoscience is highly dependent on place, and place-based curricula and instructional methods apply to geoscience education. The sense of place operationalizes the human connection to place and functions as a definable and measurable learning outcome for PBE. Although PBE is rooted in historic and indigenous teaching philosophies, it has gained particular notice and traction in concert with more recent interest in environmental education, sustainability, and diversity in geoscience. This paper presents a current review of theory and research methods that have directly informed development of curriculum and instruction in, authentic assessment of, and implementation of PBE in geoscience sensu lato (Earth-system and environmental sciences); a survey of place-based teaching in geoscience currently or recently practiced across different grade levels and situated in different places, regions, and cultures; information about teaching and assessment methods for those who may be interested in adopting the place-based modality; and suggested future directions for research, practice, and assessment in PBE in geoscience.